Enhancing task management in scrum-agile using hybrid requirement prioritization technique - Che Wil, Che Suhana (2019)
Requirement prioritization is a crucial process in Requirement Engineering which can contributes to project success. There are several requirement prioritization techniques practiced in Scrum-Agile environment. However, selecting an appropriate technique which can satisfy a quality factor such as scalability, effectiveness and efficiency can be difficult. Besides that, this technique becomes too difficult, if the stakeholders are distributed in different places and moreover, most of stakeholders tend to neglect this activity because they are busy with their routines and sometime they thinks this technique are too complex to be executed. In this study, we discusses strengths and weaknesses of the existing prioritization techniques and we also proposed a hybrid requirement prioritization technique which a combination of cumulative voting and Volere techniques, called a VoVo technique. The VoVo technique offers a structurally guided prioritization technique which can encourage user participation in prioritization process and also can mitigating the scalability issues especially in geographically distributed project. This hybrid technique is using 2 tiers prioritization process where in the first tier, the prioritization will be done by stakeholders while in the second tier requirements will be prioritized by an experts usually a scrum master or project manager. In the first tier, VoVo offers a simple and fun prioritization activity which can attract client to participate in this activity. It has been embedded in web based task management tool (scrum board) where are accessible in world wide. In the second tier prioritization activity, there are a several cost-risk factors shall be considered by an expert and also each factor will be weighted based on his/her justification. These cost-risk factors and weights maybe different for each project. The priority rate will be calculated quantitatively and the requirement which have highest rate will be displayed on the top of requirement list. This web based task management tool been evaluated through evaluation survey which been addressed directly to scrum practitioners. Its suitability and effectiveness in managing and prioritizing requirement in Sprint Backlog will be measured based on testing and evaluation survey feedbacks. Hence, we can conclude the stakeholder’s participation in requirement prioritization is important and based on evaluation survey feedbacks, proved the VoVo technique is suitable to be used for managing and prioritizing requirement in Scrum project.